Bases of development of journalistic profession in practical activities (Herald of Journalism, 2020)
Life proves that in journalism, first of all, skills and aspirations are nec- essary. Faculty wall newspaper, television station, radio studio have to work not worse, than professional mass media of our republic. Students as future professionals have to work not only at the level of university, but also at the level of journalists of foreign countries. Adopting experience of foreign colleagues, students have to develop practical skills daily.
Keywords: practice, foreign journalism, creativity, ethics of journalists.